2003
DOI: 10.1128/jvi.77.20.11284-11289.2003
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ Untranslated Region of Alfalfa Mosaic Virus RNA 1 Is Involved in Negative-Strand RNA Synthesis

Abstract: The three genomic RNAs of alfalfa mosaic virus each contain a unique 5 untranslated region (5 UTR). Replacement of the 5 UTR of RNA 1 by that of RNA 2 or 3 yielded infectious replicons. The sequence of a putative 5 stem-loop structure in RNA 1 was found to be required for negative-strand RNA synthesis. A similar putative 5 stem-loop structure is present in RNA 2 but not in RNA 3.Alfalfa mosaic virus (AMV) is a positive-strand tripartite RNA virus belonging to the family Bromoviridae (reviewed in reference 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The conserved RNA structures also commonly occur in the 5Ј UTR, or even within coding regions (8,35), involved in RNA replication (5,7,32,36,37,50,52,54,58), translation (28,30,58), virion assembly (7), adaption (5), virulence (15), or even small interfering RNA-or microRNA-mediated destruction (34). The HV region in the 5Ј UTR of satBaMV isolates identified phylogenetic groups (57) whose divergence may be a result of independent evolution in a distinct host-helper-satBaMV relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved RNA structures also commonly occur in the 5Ј UTR, or even within coding regions (8,35), involved in RNA replication (5,7,32,36,37,50,52,54,58), translation (28,30,58), virion assembly (7), adaption (5), virulence (15), or even small interfering RNA-or microRNA-mediated destruction (34). The HV region in the 5Ј UTR of satBaMV isolates identified phylogenetic groups (57) whose divergence may be a result of independent evolution in a distinct host-helper-satBaMV relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our present results also suggest the involvement of the satC 5ЈGG in initiation of minus-strand synthesis in vitro. Published studies using a variety of viral genomic RNA and subviral RNA replicons also support a role for the 5Ј end in minus-strand synthesis, through either protein-protein bridges, direct RNA-RNA interactions, or proposed 5Ј stabilization of 3Ј elements (4,14,23,31,61,66,69). Deletion of the satC 5ЈGG resulted in the synthesis of many additional products in the absence of any other alterations.…”
Section: Discussionmentioning
confidence: 99%
“…3Ј-proximal sequences comprising diverse forms such as tRNA-like structures, poly(A) tails, pseudoknots, hairpins, and short primary sequences without high-order structures have been identified as core promoters for minus-strand synthesis (11). Involvement of 5Ј-proximal sequences and structural elements in minusstrand synthesis has also been found for an increasing number of viruses (4,14,23,31,61,66,69). In addition, since plus strands cannot be templates for further translation during active replication (15), viral RNAs must contain the necessary information to switch between replication and translation as well as to support asymmetric synthesis of plus and minus strands, requirements that may include transcriptional enhancers (36,39,42,43) and repressors that function via RNA-RNA (39) or protein-RNA (11,73) interactions.…”
mentioning
confidence: 99%
“…For instance, targeting of Brome mosaic virus RNA2 to replication complexes requires a hairpin in its 5Ј UTR (4). In Poliovirus (1,11), Sindbis virus (7), and Alfalfa mosaic virus (26), 5Ј UTR elements promote negative-strand synthesis, and for Potato virus X (14), an RNA structure in its 5Ј UTR facilitates positive-strand synthesis. For TBSV, analyses of positive-and negative-strand DI RNA accumulation levels in this and other studies have not revealed any strand-specific functions for the TSD, SL5, or the DSD (23).…”
Section: Discussionmentioning
confidence: 99%